Mengintegrasikan AI based speaking tools dalam meningkatkan kemampuan speaking mahasiswa Ma’had Al Jami’ah secara berkelanjutan - Nugraha Kholid, Moh. Fikri; Irawansyah, Irawansyah; Suci Suryawati, Sri; Hidayat , Agus; Aryanika, Septa (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
This community service program was conducted at Ma’had Al-Jamiah, UIN Raden Intan Lampung, involving 45 students from various faculties. The initiative was driven by the urgent need to address challenges in mastering English speaking skills, which often hinder students' academic and professional competencies. The primary objective was to introduce, train, and guide participants in utilizing AI-based speaking tools such as ELSA Speak and Duolingo. These tools are positioned as scalable, adaptive solutions for independent language practice, aiming to enhance oral proficiency. Key issues identified prior to the program included low self-confidence, limited opportunities for speaking practice in formal settings, and a lack of access to instant, objective feedback. Evaluation results indicated a significant improvement in participants' self-confidence and pronunciation accuracy, as measured through pre-test and post-test comparisons, along with satisfaction survey analysis. Approximately 85% of participants reported that AI-based tools facilitated their learning process, provided constructive feedback, and could be flexibly integrated into their daily academic routines. These findings underscore the considerable potential of integrating AI technology into language education to foster a more inclusive, personalized, and effective learning environment.